Comparation Between Project Based Learning Aided “Edmodo” and Conventional Learning for Learning Outcomes of Two Dimentional Animation Techniques (Experimental Eleventh Grade Students of Vocational High School) - Qoris Hizbullah; A G Tamrin; Taufiq Lilo Adi Sucipto (Journal of Informatics and Vocational Education, 2018)
This research is aimed to find out:  (1) the differences learning outcomes between project based learning aided edmodo model  and conventional learning (2) the effectiveness of using project based learning model to increase learning outcomes of two dimentional animation techniques. This research used quasi experimental with pretest-posttest control group design. The population of this research are students of class XI 1 and XI 3 multimedia program of Vocation High School Batik 2 Surakarta with 70 students. The technique of data collection used test to find out cognitive value and observation to find out affective and psychomotor values. The data analysis used were t-test formula and gain index analysis. The result showed that : (1) there was difference learning outcomes between project based learning model and conventional learning model at eleventh grade students of vocational high school Batik 2 Surakarta which shown by t_count= 4,435 cognitive, t_count= 2,175 affective, t_count  = 2,344 psychomotor were bigger that t_table = 1,995. (2) project based learning is more effective than conventional learning model to increase learning outcomes of two dimentional animation techniques which shown by gain index analisys, at experiment class obtained 0,587 and control class obtained 0,369.